2015
DOI: 10.1016/j.marmicro.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability of benthic foraminiferal assemblages and metal concentrations during the last 150years in the Ingøydjupet trough, SW Barents Sea

Abstract: While today the SW Barents Sea is a relatively un-impacted and uncontaminated area, industrial activities related to the petroleum industry are projected to increase in the coming decades. This makes the area a valuable natural laboratory to establish pre-impacted baselines as a precursor for future seabed monitoring programs. Here we present benthic foraminiferal assemblages and metal concentrations in four sediment cores from the Ingøydjupet trough, SW Barents Sea, covering approximately the last 150 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 63 publications
5
23
1
Order By: Relevance
“…5). Other studies have also reported an increase in PAH as well as heavy-metal concentrations which correlates with an increase in TOC and the fraction of fine-grained material (Boitsov et al, 2009a;Dijkstra et al, 2013Dijkstra et al, , 2015. This supports the idea that PAH concentrations respond to natural variability in the transportation of sediments by bottom currents (Junttila et al, 2014).…”
Section: Figure 8 Relationship Between Pah Ratios and The Identificasupporting
confidence: 74%
See 4 more Smart Citations
“…5). Other studies have also reported an increase in PAH as well as heavy-metal concentrations which correlates with an increase in TOC and the fraction of fine-grained material (Boitsov et al, 2009a;Dijkstra et al, 2013Dijkstra et al, , 2015. This supports the idea that PAH concentrations respond to natural variability in the transportation of sediments by bottom currents (Junttila et al, 2014).…”
Section: Figure 8 Relationship Between Pah Ratios and The Identificasupporting
confidence: 74%
“…Bottom current transportation of fine-grained sediments and heavy-metal concentrations based on the same sample material as presented in this paper has been studied previously (Dijkstra et al, 2013(Dijkstra et al, , 2015Junttila et al, 2014). Through these earlier studies, there is a clear connection between bottom current strength, fine particle deposition, and heavy-metal concentrations.…”
Section: Tocmentioning
confidence: 73%
See 3 more Smart Citations